Determination Causes of Tax Avoidance on Indonesian Manufacturing Firms with Capital Intensity as Intervening Variables - Theresia Trisanti (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2021)
The aim of this study is to examine and analyze the effect of the independent variables, namely return on assets (ROA), debt to assets ratio (DAR), company size, and capital intensity on the dependent variable in the form of tax avoidance. The population in this study was manufacturing companies listed on the Indonesia Stock Exchange for the period 2016 - 2019. By using purposive sampling technique, data analytical technique used is descriptive statistic, classic assumption test and hypothesis testing in the form of SmartPLS analysis. The test results show that the variables return on assets (ROA), debt to assets ratio (DAR), company size, and capital intensity affect the tax avoidance. Capital intensity can mediate the relation for variable return on assets (ROA), debt to assets ratio (DAR), company size to tax avoidance.